Engaging young adults in fostering entrepreneurial mind-set using the community education approach: Case study of chorkor community, Ghana. (4th May 2023) - Biney, Isaac Kofi
ABSTRACT: This paper draws on McGivney's study of adult education for marginal groups, including unemployed young adults. The young unemployed adults in Ghana are growing in numbers; hence engaging them using the community education to foster entrepreneurial mind-sets is a means of addressing the unemployment problem. The formation of learning groups helps foster self-help and enhances the contributions of diverse synergies to community development and transformation. This qualitative case-study used young adults between the ages of 18 to 35 at Chorker, Accra, as the unit of analysis. Judgmental sampling techniques were adopted to sample fourteen (14) participants to participate in the study. They consist of 8 participants for in-depth interview and 6 participants comprising three (3) male and three (3) female formed focus group discussions. Data was analyzed using descriptive narrative and interpretivist approaches. The results indicate that the participants were empowered as they engaged in group learning to acquire skills in trades. The study recommends that young adults are motivated to engage in community education to foster entrepreneurial mind-set, innovate and exploit opportunities to make their communities more vibrant and sustainable.